ANALISIS PENGARUH VARIASI PENGGUNAAN BAHAN BAKAR PERTAMAX DAN PERTALITE TERHADAP PERFORMA DAN KONSUMSI BAHAN BAKAR PADA MOTOR FIT X 100 CC TAHUN - Putri Sundari, M.T; Sugeng Hariyadi, M.T; Mohammad Fatichul Ilmi, ST (Wahana Teknik, 2021)
This study aims to determine the effect of Pertamax 92 and Pertalite 90 fuels on the power and torque performance of the 2008 100 cc Supra Fit X motorbike and also to obtain precise data regarding the percentage of fuel consumption tests obtained from Pertamax 92 and Pertalite 90 fuels. This is done by dyno test and also fuel consumption test. From the results of the dyno test, the torque results from pertamax fuel are 15.37 N/m and from pertalite fuel the torque results are 14.81 N/m while for the power from Pertamax fuel is 14.53 HP and for power from Pertamax fuel is 14.53 HP. pertalite fuel of 13.88 HP. And for the test results of Pertamax and Pertalite fuel consumption. Pertamax fuel is classified as more efficient than pertalite fuel with test results of fuel consumption of 0.242 ml / s while pertalite fuel is 0.244 ml / s